A new Asian horned toad of the genus Jingophrys (Amphibia, Megophryidae) from Xizang, China - Yuan, Xinhai; Chen, Jinmin; Ai, Renda; Lu, Wenzhu; Liu, Xiaolong; Zhou, Weiwei; Huang, Junkai; Yuan, Zhiyong (Zootaxa, 2026)
A new species of the genus Jingophrys is described from Xizang, China based on the morphological comparisons and phylogenetic reconstruction. Morphologically, this new species Jingophrys zhaoermii sp. nov. can be distinguished from other known congeners by a combination of diagnostic characteristics: (1) body size small, SVL 34.5–35.4 mm in adult males and SVL 39.6–43.1 mm in adult females; (2) tympanum distinct, upper margin slightly concealed by supratympanic fold; (3) presence of weak vomerine ridge, absence of vomerine teeth; (4) tongue notch absent; (5) hindlimbs slender, heels meeting when thighs flexed at right angles to the axis of body and tibiotarsal articulation reaching anterior corner of eye or tip of the snout when leg stretched alongside body; (6) fingers with lateral fringes, subarticular tubercles absent; (7) toes with rudimentary webbing at bases and lateral fringes; (8) dorsal skin relatively smooth (lack granules), strong discontinuous X-shaped ridge on center of dorsum, discontinuous dorsolateral ridges absent or weak; (9) sparse large tubercles on flanks, no granules between tubercles; (10) adult males lack nuptial pads. Phylogenetically, it differs from its congeners by uncorrected p-distances of >3.7% for the 16S gene fragment and uncorrected p-distances of >10.1% for the COI gene fragment. Additionally, we provide a new identification key to the genus Jingophrys.